Do Cognitive Patterns of Strengths and Weaknesses Differentially Predict Errors on Reading, Writing, and Spelling?. (February 2017) - Liu, Xiaochen; Marchis, Lavinia; DeBiase, Emily; Breaux, Kristina C.; Courville, Troy; Pan, Xingyu; Hatcher, Ryan C.; Koriakin, Taylor; Choi, Dowon; Kaufman, Alan S.
This study investigated the relationship between specific cognitive patterns of strengths and weaknesses (PSWs) and the errors children make in reading, writing, and spelling tests from the Kaufman Test of Educational Achievement–Third Edition (KTEA-3). Participants were selected from the KTEA-3 standardization sample based on five cognitive profiles: High Crystallized Ability paired with Low Processing Speed and Long-Term Retrieval (High Gc ), Low Crystallized Ability paired with High Processing Speed and Long-Term Retrieval (High Gs / Glr ), Low Orthographic Processing (Low OP), Low Phonological Processing (Low PP), and Low Phonological Processing paired with Low Orthographic Processing (Low PP_OP). Error factor scores for all five groups were compared on Reading Comprehension and Written Expression; the first four groups were compared on Letter & Word Recognition, Nonsense Word Decoding, and Spelling, and the first three groups were compared on Phonological Processing. Significant differences were noted among the patterns of errors demonstrated by the five groups. Findings support the notion that students with diverse cognitive PSWs display different patterns of errors on tests of academic achievement.